Our planet powered by AI : how we use artificial intelligence to create a sustainable future for humanity - Minevich, Mark (Ascent Audio, 2023)
A hands-on guide to evolving your company with ethical AI along with thought-provoking insights and predictions from a variety of well-known industry leaders. In Our Planet Powered by AI, renowned AI strategist and pioneer Mark Minevich delivers an exciting and practical discussion of how to implement groundbreaking artificial intelligence technologies at every level of your organization. You'll learn to create sustainable, effective competitive advantage by introducing previously unheard-of levels of adaptability, resilience, and innovation into your company. Using real-world case studies from a variety of well-known industry leaders, the author explains the strategic archetypes, technological infrastructures, and cultures of sustainability you'll need to ensure your firm's next-level digital transformation takes root. You'll also discover: - How AI can enable new business strategies, models, and ecosystems of innovation and growth - How to develop societal impact and powerful organizational benefits with ethical AI implementations that incorporate transparency, fairness, privacy, and reliability - What it means to enable all-inclusive artificial intelligence.